DETERMINAN PERSEPSI MAHASISWA AKUNTANSI MEMILIH PROFESI AKUNTAN - THYO YOHANA BR MANIK; ZUL AZMI; WIRA RAMASHAR (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2022)
This study aims to determine the determinants of accounting students' perceptions of choosing the accounting profession. Variables such as students' perceptions of choosing the accounting profession include negative attitudes of accountants, professional image, accountants' work results, accountants' job requirements, and work environment are considered to be related to student preferences. The questionnaire survey method was conducted for final year students using the saturated sampling method. The survey was conducted on 171 students of the Accounting study program at the Muhammadiyah University of Riau. Data were analyzed using multiple regression. The results show that the negative attitude of accountants has a significant negative effect on students' perceptions of choosing the accounting profession. The image of the accounting profession, the work of accountants, the job requirements of accountants have a significant effect on the perception of accounting students choosing the accounting profession. Likewise, the work environment of accountants has a significant effect on students' perceptions of choosing the accounting profession